Analisis Perbandingan Dampak Lingkungan Budidaya dan Pengolahan Biji Kopi Robusta Pagar Alam Menggunakan Pendekatan Life Cycle Asessment (LCA) - Susanti, Novia; Romli, Muhammad; Yani, Mohamad (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2026)
Pagar Alam Robusta coffee contributes significantly to the regional economy. Its cultivation and processing systems pose environmental challenges. This study compares the environmental performance of two cultivation methods (conventional-K1 and non-pesticide-K2) and six processing methods (natural origin-A1, broken skin origin-A2, natural aerobic-N1, natural anaerobic-N2, honey aerobic-H1, and honey anaerobic-H2). A cradle-to-gate Life Cycle Assessment (LCA) was conducted using a functional unit of 100 kg of green coffee beans, covering four impact categories: global warming potential (GWP), ozone depletion potential (ODP), acidification potential (AP), and eutrophication potential (EP). In the cultivation subsystem, K1 produced emissions of 85.70–117.00 kg CO₂-eq (GWP), 3.53×10-6–4.80×10-6 kg CFC-11-eq (ODP), 0.37–0.50 kg SO₂-eq (AP), and 0.16–0.22 kg PO₄-eq (EP), while K2 produced much lower emissions: 23.00–31.30 kg CO₂-eq (GWP), 2.22×10-7–3.03×10-7 kg CFC-11-eq (ODP), 0.09–0.13 kg SO₂-eq (AP), and 0.03–0.04 kg PO₄-eq (EP). In the processing subsystem, H2 had the highest emissions: 14.77 kg CO₂-eq (GWP), 6.48 kg CFC-11-eq (ODP), 0.04 kg SO₂-eq (AP), and 0.02 kg PO₄-eq (EP), while A1 had the lowest emissions: 5.23 kg CO₂-eq (GWP), 3.87 kg CFC-11-eq (ODP), 0.01 kg SO₂-eq (AP), and 0.001 kg PO₄-eq (EP). Implementing an improvement scenario based on non-pesticide cultivation (K2) could reduce emissions by approximately 65–93% across all impact categories. These findings demonstrate that adopting pesticide-free cultivation combined with simpler processing methods can significantly reduce the environmental footprint of Robusta coffee production in Pagar Alam and support more sustainable coffee management practices.